Urgent and Nonurgent Presentations to a Psychiatric Emergency Service in Nigeria: Pattern and Correlates - Increase Ibukun Adeosun; Abosede Adekeji Adegbohun; Oyetayo Oyewunmi Jeje; Olufemi Oyeleke Oyekunle; Modupeola Olugbemisola Omoniyi (Emergency Medicine International)
Psychiatric emergencies are acute mental health disturbances that require immediate intervention. However, the emergency department is increasingly being utilised for nonurgent mental health problems, thereby compromising the quality of care available for patients with urgent problems. This study assessed the level and correlates of urgency of mental health problems among patients presenting to an emergency department in Nigeria. The Crisis Triage Rating Scale, Clinical Global Impression Scale and a supplementary questionnaire were administered to 700 attendees at the emergency department of the Federal Neuro-Psychiatric Hospital Yaba, Lagos. Only 29.1% of the presentations constituted an “emergency” 10.9% were “urgent,” while 60% were “nonurgent.” The most common reason for nonurgent presentations was the need for medication refill. On regression analysis, level of urgency of presentations was independently associated with employment status, need for medication refill, substance abuse, suicidality, routine clinic attendance, and use of physical restraint before presentation. The majority of visits to the emergency department are for apparently “nonurgent problems.” However in a resource-poor setting, the emergency department may be the only safety net for the attendees. Our findings point to a need for education of service users and policy shifts in mental health care financing and organisation.